Analysis of Cantilever Retaining Wall as Landslide Mitigation on a Tributary of Cisadane River Bogor City - Lutfi, Muhamad; Chayati, Nurul; Rulhendri, Rulhendri; Taqwa, Fadhila Muhammad Libasut; Ramadan, Fahreza Rahmatsyah (ASTONJADRO, 2023)
Bogor City has a high level of rainfall and is included in an area with a high potential for landslides. In March 2021, there was a landslide in a densely populated residential area at RT. 02/03 Cipaku Village, Bogor Selatan District. The landslide occurred on the slopes at the tributary of Cisadane River and adjacent to the nearest connecting bridge. The length of the landslide is 6 meters and as high as 7 meters from the water surface. Mitigation steps to prevent subsequent landslides are needed by constructing a retaining wall, so a cantilever-type retaining wall is chosen by considering the soil parameters and landslide conditions. The results of the analysis show that the stability of the retaining wall against shear (Fs) = 1.04 < SF = 1.5 and for stability against overturning (Fo) = 0.56 < SF = 1.5. Thus, the overall retaining wall is not able to withstand the load of the soil behind it. In terms of stability to the bearing capacity of the soil, the ultimate soil capacity (qs) = 94.149 kN/m2 > V = 243.535 kN/m2. Thus, the subgrade can withstand the load of the retaining wall. Therefore, to meet shear stability and overturning stability, the retaining wall is reinforced by using a bored pile foundation. The results of the foundation analysis showed that the allowable capacity (Qs) was obtained at 584.8 kN.